EFFECT OF FOLIAR NUTRITION OF HUMIC ACID AND CHELATED IRON IN GROWTH AND YIELD OF BROAD BEANS (Vicia faba L.) - Hamood, Amjed Shaker; Jumaah, Najm Abdullah (Diyala Agricultural Sciences Journal, 2018)
A factorial experiment (RCBD) with three replications. This study has been done in Diyala governorate, Al-Muqdadia, Abi-Sayda, during the winter season 2015-2016 using sandy clay loam soil. The aim of this study was to know the effect of foliar nutrition of three levels for each one humic acid 0, 1 and 2 ml l-1 and chelated iron 0, 100 and 200 mg Fe l-1, on the growth and yield of Vicia faba L. "Luzde otono". The results showed that spraying humic acid with the concentration 2 ml l-1 outplayed in leaf area, dry weight, flowers number, pods number, pod length, number of seeds in a pod, pod weight, weight of 100 seeds and yield per plant which reached 2151.79 cm2 plant-1, 27.26 g plant-1, 45.81 flower plant-1, 10.83 pod plant-1, 25.34 cm, 5.04 seed pod-1, 48.73 g, 384.64 g and 310.25 g, respectively as compared with the control treatment. While in spraying chelated iron, the concentration 200 mg Fe l-1 outplayed in plant height, leaves number, leaf area, dry weight, flowers number, pods number, pod length, pod weight and yield per plant, which reached 119.02 cm, 30.39 leaf plant-1, 2107.57 cm2 plant-1, 27.17 g plant-1, 44.66 flower plant-1, 10.23 pod plant-1, 25.25 cm, 48.54 g and 304.93 g plant-1, respectively as compared with control treatment. The interpenetration of 2 ml l-1×200 mg Fe l-1 showed a significant effect in most attributes.